Disability and primary health care: from knowledge to invencion of praxis - Almeida, Marta Carvalho de; Tissi, Maria Cristi; Oliver, Fátima Corrêa (Revista de Terapia Ocupacional da Universidade de São Paulo, 2000)
There is an increasing demand for more knowledge on the problem of disabilities in speeifíc contexts. This demand is impelled by some statements made eoneeming the relationship between rehabilitation and Primary Health Care, as well by the difusion of Community Based Rehabilitation. A door-to-door survey (100%) was condueted in the periphery of São Paulo city, to direct the planning ofrehabilitation for a primary health care service, whose responsability lies in this area. In this first paper we show and diseuss the role of this results. Informations on the characteristies and situation ofpeople suffering from physical and sensory limitations were essential to define the role of the health service. The pattems of the utilization of health or rehabilitation services, the schooling and work situations and the limitations derived by architectural barriers revealed that most of that group suffers from social disadvantage. This made clear that the primary health service task is to develop practices highly integrated into the community. The results of the research and discussion about the praxis adopted are presented in this paper.